FAO fisheries report N543: Report of the 8th session of the WCAFC, held at Caracas, Venezuela, 20-24 November 1995 (FAO, 1996)
This document is the final version of the report of the 8th session of the WECAFC. Major topics were: the current situation of fisheries in the region and prevailing trends, the possible role of WECAFC to ensure effective conservation, management and development of fisheries in the region. The Session analyzed and adopted the report of the Committee for the Management and Development of Fisheries in the Lesser Antilles. The Commission also reviewed the main activities carried out as the result of the decisions and recommendations made for the intersessional period and agreed on the programme for the forthcoming biennium taking into account the restructing and decentralization process in FAO as well as the financial situation of the Organization.